Strategy of Logoplaste in Mozambique's flexible plastic packaging industry - Miranda, Leonor Sereno Condesso Souto (2015)
Logoplaste is a specialist in operating in-house industrial sites for manufacturing rigid plastic packaging containers. In developing countries, especially in Africa, the low income of consumers does not allow a widespread adoption of products typically sold in rigid plastic containers. In these countries the flexible packages are usually adopted as they allow for better ratios of cost/litter of product, particularly in smaller packages. Should Logoplaste offer this type of technology in order to expand into developing countries?